Prevalence of β-lactamase production and multi-drug resistance among uropathogenic Escherichia coli isolates at a tertiary care hospital of North-western India - Jain, Ruchi; Pal, Nita; Hooja, Saroj (Asian Journal of Medical Sciences, 2021)
Background: E.coli is the most common organism causing UTI. Inappropriate and widespread use of broad-spectrum antibiotics has resulted in development of multi-drug resistance and β-lactamases producing strains. Aims and Objective: To assess β-lactamase production and multi-drug resistance among uropathogenic E.coli isolates. Materials and Methods: A total of 145 E.coli urinary isolates were included in this study. The isolated organisms were identified by conventional microbiological procedures. Antimicrobial susceptibility was performed by Kirby Bauer disk diffusion method. Isolates were screened for extended spectrum β-lactamase production and confirmed by phenotypic confirmatory double disc synergy test. Isolates resistant to cefoxitin were considered potential AmpC producers confirmed by AmpC disc test and modified three dimensionsl test. Isolates resistant to imipenem and meropenem were considered potential carbapenemase producers and confirmed by mCIM test. Results: Out of 145 isolates 91 (62.76%) were isolated from males and 54 (37.24%) from females. Majority of the isolates were obtained from the age group of 21-30 years (48.96%) followed by 31-40 years (14.48%). Highest susceptibility was seen towards fosfomycin (94.48%), tigecycline (87.59%), nitrofurantoin (77.24%). Highest resistance of 81.38% was observed against ampicillin while more than 70.0% resistance observed with cefazolin, cefotaxime, ciprofloxacin, levofloxacin and amoxiclav. Multi-drug resistance was observed in 85.51% isolates and 4.14% were found to be possible XDR. Among these isolates frequency of β-lactamase production was ESBL (45.51%), AmpC (28.96%) and caebapenemase (28.96%). Conclusion: Drug resistance due to β-lactamases production is emerging as a serious threat in UTI; routine screening of these β-lactamases will prevent treatment failures.